2022
DOI: 10.1002/rmv.2373
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into SARS‐CoV‐2 omicron variant

Abstract: The SARS‐CoV‐2 omicron variant (B.1.1.529) was first identified in Botswana and South Africa, and its emergence has been associated with a steep increase in the number of SARS‐CoV‐2 infections. The omicron variant has subsequently spread very rapidly across the world, resulting in the World Health Organization classification as a variant of concern on 26 November 2021. Since its emergence, great efforts have been made by research groups around the world that have rapidly responded to fill our gaps in knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 159 publications
1
33
0
Order By: Relevance
“… 629 631 More recently, we have revised in detail the SARS-CoV-2 omicron variant and several characteristics related to this novel variant. 632 …”
Section: Emerging Variants Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“… 629 631 More recently, we have revised in detail the SARS-CoV-2 omicron variant and several characteristics related to this novel variant. 632 …”
Section: Emerging Variants Of Sars-cov-2mentioning
confidence: 99%
“…The omicron VOC displays distinct biological characteristics, including strong binding to human ACE2 receptor and high transmissibility, despite being less virulent than the original strain or the previous VOCs. In addition, the omicron VOC displays high environmental stability and high resistance against clinically approved monoclonal antibodies and immunity elicited by natural infection or vaccination. More recently, we have revised in detail the SARS-CoV-2 omicron variant and several characteristics related to this novel variant …”
Section: Emerging Variants Of Sars-cov-2mentioning
confidence: 99%
“…The recently evolved SARS-CoV-2 Omicron variant has been shown to exhibit increased transmissibility and escape from humoral immunity generated by previous infections and vaccines [ 1 , 2 , 3 , 4 ]. Importantly, accumulating clinical–epidemiological observations demonstrated that Omicron is associated with a milder disease compared with Delta and earlier variants of concern (VOC) [ 2 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A new wave of a subvariant of concern of the “omicron” variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)—which poses very high risk of infection—is spreading worldwide, continuing the evolving pandemic that is now in its third year [ 1 ]. The efficacy of current vaccines against this heavily mutated variant is still unclear [ 2 ].…”
Section: Introductionmentioning
confidence: 99%